Musictone Entertainment / Mohammad Hazwan Abu Hassan ... [et al.] - Abu Hassan, Mohammad Hazwan; Mohd. Noor, Nor Helina; Ismail, Siti Zuraidah; Maarof, Iwani; Ahsan, Nor Diana (Faculty of Office Management & Technology, 2004)
MUSICTONE ENTERTAINMENT is a local partnership company business. It consists of 5 partnership members. This business basically focuses on selling cassettes, compact discs and magazines related to music entertainment not only locally but also internationally. We also sell our own products as souvenirs such as MUSICTONE tshirt, towels, mugs and key chains.